Chemoradiation therapy alters the PD-L1 score in locoregional recurrent squamous cell carcinomas of the head and neck. (December 2022) - Park, Brian J.; Mattox, Austin K.; Clayburgh, Daniel; Patel, Mihir; Bell, R. Bryan; Yueh, Bevan; Leidner, Rom; Xiao, Hong; Couey, Marcus; Li, Shiting; Qin, Tingting; Sartor, Maureen A.; et al.
Highlights: PD-L1 testing, as reported as CPS, guides therapeutic decision-making for head and neck cancers. When using a CPS ≥ 20, there was a 32 % change in CPS score when comparing the primary site to the site of locoregional recurrence. Oral cavity cancers had a significantly higher discordant rate in CPS after chemoradiation therapy. Repeat biopsy should be considered for locoregional recurrent head and neck cancers if using CPS ≥ 20. Abstract: PD-L1 testing guides therapeutic decision-making for head and neck squamous cell carcinoma (HNSCC). We sought to understand whether chemoradiation therapy (CRT) influences the PD-L1 combined positive score (CPS) and other biomarkers of response to immunotherapy. PD-L1 expression was assessed using immunohistochemistry, and bulk RNA sequencing was performed on 146 HNSCC patients (65 primary sites, 50 paired local recurrences, and 31 paired regional recurrences). PD-L1 was scored using the CPS of ≥1, ≥20, and ≥50. Overall, 98 %, 54 %, and 17 % of HNSCCs had a CPS ≥1, ≥20, and ≥50, respectively. When using a cut-off of ≥1, CRT did not significantly change CPS at the locoregional recurrent site. However, there were significant changes when using CPS ≥20 or ≥50. The CPS changed for 32 % of patients when using a CPS ≥20 ( p < 0.001). When using a CPS ≥50, there was a 20–23 % ( p = 0.0058–0.00067) discordance rate at the site of locoregional recurrence. Oral cavity cancers had a significantly higher discordant rate than other primary sites for CPS ≥50, 44 % (8/18, p = 0.0058) and 58 % (7/12, p = 0.00067) discordance at the site of local and regional recurrence, respectively. When evaluating the 18 gene IFN-ɣ signature predictive of response to anti-PD-1 blockade, there was a statistically significant increase in the IFN-ɣ signature in recurrent larynx cancer ( p = 0.02). Our study demonstrates that when using a higher cut-off of CPS ≥20 and ≥50, a repeat biopsy may be warranted after CRT for local and regional recurrent HNSCCs.